2018 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--30957
|View full text |Cite
|
Sign up to set email alerts
|

Senior Civil Engineering Students’ Views on Sustainability and Resiliency

Abstract: where he is a member of the Electrical and Computer Engineering Department and IDoTeach, a pre-service STEM teacher preparation program. His work focuses on the transition from pre-college to university engineering programs, how exposure to engineering prior to matriculation affects the experiences of engineering students, and engineering in the K-12 classroom. He has worked as a high school science, mathematics, and engineering and technology teacher, as well as several years of electrical and mechanical engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…With the growing demand to address climate change impacts, such knowledge is critical for the future engineering workforce to develop a resilient built environment. Very few studies have discussed educating students about resilient design solutions against flood disasters (Lopez del Puerto et al , 2019; Pagán-Trinidad et al , 2019; Salzman et al , 2018). Although these studies have adopted resilience concepts through different teaching approaches, there remains a gap in introducing the resilient urban design concept, SF, to AEC students and assessing their interest to learn such concepts.…”
Section: Introductionmentioning
confidence: 99%
“…With the growing demand to address climate change impacts, such knowledge is critical for the future engineering workforce to develop a resilient built environment. Very few studies have discussed educating students about resilient design solutions against flood disasters (Lopez del Puerto et al , 2019; Pagán-Trinidad et al , 2019; Salzman et al , 2018). Although these studies have adopted resilience concepts through different teaching approaches, there remains a gap in introducing the resilient urban design concept, SF, to AEC students and assessing their interest to learn such concepts.…”
Section: Introductionmentioning
confidence: 99%
“…Civil engineers, in particular, should demonstrate an understanding of sustainability to prepare them to address global challenges, promote ethical practices, meet industry trends, and exhibit problem-solving skills. Interviews with senior-level civil engineering students at a higher education institution revealed that they did not learn how sustainability was related to their coursework (Salzman et al, 2018). Accreditation agencies such as Accreditation Board for Engineering and Technology (ABET) incorporate sustainability-related student outcomes into their criteria requiring that students have "an ability to apply engineering design to produce solutions that meet specified needs with consideration of public health, safety, and welfare, as well as global, cultural, social, environmental, and economic factors" also students should have "an ability to recognize ethical and professional responsibilities in engineering situations and make informed judgments, which must consider the impact of engineering solutions in global, economic, environmental, and societal contexts" (ABET, 2021).…”
Section: Introductionmentioning
confidence: 99%